ANALYSIS OF SERUM BILIRUBIN/ SERUM ALBUMIN RATIO IN NEONATAL HYPERBILIRUBINEMIA AMONG PREMATURE NEONATES - Seema Darotiya; Gayatri Yadav (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background Neonatal hyperbilirubinemia or neonatal jaundice is a common and potentially serious condition, particularly in premature infants. It is characterized by elevated levels of bilirubin in the blood, which can cause jaundice—a yellowish discoloration of the skin, sclera, and mucous membranes. Neonatal hyperbilirubinemia is the most commonly encountered medical problem in the first two weeks of life and a common cause of readmission to the hospital after birth. [1] Approximately 60% of full-term and 80% of preterm newborns develop jaundice in their first week of life.[2] Over the years, the understanding of neonatal jaundice has evolved, encompassing both severe and milder forms.[3] While jaundice is often a benign and self-limiting condition, known as "physiological jaundice," it can also present as "pathological jaundice" when bilirubin levels rise to dangerous levels. In severe cases, this can lead to complications such as bilirubin encephalopathy or kernicterus, which can result in long-term neurological damage or even death. Premature neonates are at an even greater risk of developing severe hyperbilirubinemia due to their immature liver function, reduced albumin levels, and increased susceptibility to bilirubin neurotoxicity. The immaturity of the hepatic enzymes responsible for conjugating bilirubin contributes to the buildup of unconjugated bilirubin in the bloodstream. [4-5] This poses a significant risk to the central nervous system, particularly when free (unbound) bilirubin crosses the blood-brain barrier, leading to bilirubin-induced neurological dysfunction (BIND).[6] The bilirubin/albumin (B/A) ratio has emerged as a valuable marker for assessing the risk of bilirubin neurotoxicity in neonates with hyperbilirubinemia.[7-9] Since albumin binds to unconjugated bilirubin in the blood, the B/A ratio serves as an indirect measure of free bilirubin, which is the neurotoxic form. An elevated B/A ratio indicate a higher likelihood of unbound bilirubin being present, thus increasing the risk of neurological damage.[10] Despite the potential significance of the B/A ratio, there is limited data on its use in clinical practice, particularly in premature neonates, who are at greater risk due to lower albumin levels and higher bilirubin production. This study aims to analyze the serum bilirubin/serum albumin ratio in premature neonates with hyperbilirubinemia and to assess its potential as a clinical tool for predicting the severity of hyperbilirubinemia and the associated risk of neurological complications. By focusing on premature infants, this study seeks to provide valuable insights into the management of neonatal hyperbilirubinemia and the role of the B/A ratio in guiding treatment decisions.[11]